16 Outcomes of a novel 5-week individualized multidisciplinary outpatient (day-patient) treatment programme for functional (psychogenic) neurological symptoms. Issue 8 (20th July 2020) - Petrochilos, P; Elmalem, M; Selai, C; Patel, D; Hayward, K; Ranu, J; Louissaint, H
Abstract : Aim: We report the results of a novel 5-week treatment programme, delivered by a multi-disciplinary team, with individualised sessions to treat functional neurological symptoms in a neuropsychiatric outpatient setting. The primary aims of this MDT programme were to (a) reduce symptoms (b) improve health and social functioning (c) improve functional performance (d) improve health status. Method: Treatment involved individual sessions of neuropsychiatry, cognitive behavioural therapy, physiotherapy, occupational therapy, education and family meetings. Outcome measures were collected at the beginning and end of treatment and at a 6 month face to face follow-up. These were both patient and clinician reported. The aims were assessed by the following measures: symptom reduction (PHQ15, PHQ9, GAD7, SPIN, Rosenberg, CGI); health and social functioning (HONOS, WSAS); functional performance (COPM); and improvements in health status (EQ5DL). Results: Analyses were conducted on 78 patients who started and completed the programme and attended a 6 month face to face review. There were high baseline levels of disability compared to EQ5DL population norms and high rates of disability and psychopathology as indicated by the WSAS and mental health indices (PHQ9, GAD7, SPIN, Rosenberg's self-esteem). At baseline, 92.3% met the IAPT caseness threshold for depression (PHQ9 >10) and 71% met the IAPT caseness threshold for anxiety (GAD7 >8). A repeated measures Freidman's ANOVA over 3 timepoints (admission, discharge and 6 month follow-up) followed by Dunn-Bonferroni post hoc tests indicated statistically significant improvements from admission to discharge and admission to 6 months follow up. These improvements were seen in in somatic symptoms (PHQ15), depression (PHQ9) and anxiety (GAD7) symptoms, health and social functioning (HONOS), functional performance (COPM), health status (EQ5D-5L and EQ5D-EL VAS) and patient ratings of clinical global improvement (CGI). There was a high acceptance of this neuropsychiatry led MDT programme indicated by the patient reported visual analogue scale for benefit of programme averaging at 90%. Conclusion: An MDT can effectively deliver an outpatient programme for FNS which can serve as an alternative to an inpatient programme for patients with fewer or no nursing needs, for those whose preference is an outpatient setting or for those seeking to minimise disruption to work or family life. There may be potential cost reductions for institutions compared to inpatient treatment depending on local calculations. In the future, earlier identification and treatment of co-morbidities may modify some predisposing and perpetuating factors.